1990
DOI: 10.1289/ehp.908935
|View full text |Cite
|
Sign up to set email alerts
|

Lead effects on postural balance of children.

Abstract: The postural sway responses of 63 children with a mean age of 5.74 years were quantified with a Force Platform technique. The average maximum (max) blood lead (PbB) of these children during the first 5 years of life was 20.7 ug/dL (range 9.2 to 32.5). The backward stepwise regression analysis for sway area response during the eyes-closed, no-foam test with all the covariates and confounders and the PbB parameters showed a significant relationship with peak or max PbB during the second year of life. These resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
4

Year Published

1993
1993
2005
2005

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 18 publications
(17 reference statements)
2
31
0
4
Order By: Relevance
“…Thus, a static posturography with frequency analysis of postural sway is demonstrated to be useful for assessing dose-effect relationships between neurotoxic chemicals such as lead, organic solvents and sarin, and their effects on postural balance systems, in light of results from previous studies [2][3][4][5][6][7][8][9][10][11][12][13][14][15] which revealed significant increase in the postural sway caused by chemical substances. However, there are some weaknesses in the studies presented here.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a static posturography with frequency analysis of postural sway is demonstrated to be useful for assessing dose-effect relationships between neurotoxic chemicals such as lead, organic solvents and sarin, and their effects on postural balance systems, in light of results from previous studies [2][3][4][5][6][7][8][9][10][11][12][13][14][15] which revealed significant increase in the postural sway caused by chemical substances. However, there are some weaknesses in the studies presented here.…”
Section: Discussionmentioning
confidence: 99%
“…Effects have been (63) observed at blood lead levels similar to those (28,40) in children; a no observable effect level has (28) not been identified in either children or ani- (18) mals. Research in the last decade has often included analyses to identify the behavioral (59) processes underlying the observed lead- (54) induced behavioral deficits (75). (30) Much of the earlier work in animal (36) models assessed the effects of high doses of (34139) lead on simple learning problems.…”
Section: Human Studiesmentioning
confidence: 99%
“…Some groups of investigators reported that postural balance was adversely affected by lead using a computerized static posturography [31][32][33][34][35][36][37][38] . This technique measures displacements of the body's center of pressure in a horizontal plane by the use of a force platform connected to a microcomputer; summary measures generally used were length of the sway path or speed of the sway and the area included within the sway path.…”
Section: Introductionmentioning
confidence: 99%